ХАЛЫҚ ФОЛЬКЛОРЛЫҚ ДӘСТҮРЛЕРДИ ҮЙРЕНИЎ ДӘЎИР ТАЛАБЫ (ART AND CULTURE BULLETIN, 2025)
Studying the centuries-old spiritual values of our people, important for the Third Renaissance period, is one of the pressing issues. The article reveals the historical development stages of oratory in our spiritual values, the phenomenon of improvisation, as well as the fact that this art is an important phenomenon in educating the younger generation as patriots of the Motherland, enriching their spiritual world, ensuring political-diplomatic, international relations and interethnic harmony, friendship of peoples
Keywords: national heritage; oratory; improvisation; literature; folklore; art; tradition; folklore.